2015
DOI: 10.1039/c4nr06849a
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and bio-reactivity of polystyrene nanoparticles is affected by surface modifications, ageing and LPS adsorption: in vitro studies on neural tissue cells

Abstract: Because of their capacity of crossing an intact blood-brain barrier and reaching the brain through an injured barrier or via the nasal epithelium, nanoparticles have been considered as vehicles to deliver drugs and as contrast materials for brain imaging. The potential neurotoxicity of nanoparticles, however, is not fully explored. Using particles with a biologically inert polystyrene core material, we investigated the role of the chemical composition of particle surfaces in the in vitro interaction with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 45 publications
5
54
0
Order By: Relevance
“…In a study in which NPs synthesis was repeated in normal conditions or after glassware and tool depyrogenation, we could show that taking precautions could significantly dampen the endotoxin contamination in ENM (28). On the other hand, a heavy endotoxin contamination in polystyrene ENM after long-term storage (over 6 months) may have been due to the poor handing processes (29). Thus, we should be aware that endotoxin contamination in ENM is a common phenomenon.…”
Section: Endotoxin Contamination Of Nanomaterialsmentioning
confidence: 99%
“…In a study in which NPs synthesis was repeated in normal conditions or after glassware and tool depyrogenation, we could show that taking precautions could significantly dampen the endotoxin contamination in ENM (28). On the other hand, a heavy endotoxin contamination in polystyrene ENM after long-term storage (over 6 months) may have been due to the poor handing processes (29). Thus, we should be aware that endotoxin contamination in ENM is a common phenomenon.…”
Section: Endotoxin Contamination Of Nanomaterialsmentioning
confidence: 99%
“…In previous studies, we showed that different batches of NPs synthesized following an identical protocol may have different contamination levels of endotoxin depending on the level of cleanliness during the synthesis procedure (Oostingh et al 2011). Also, we found that poor handling processes and storage under different conditions can contaminate NPs and endow them with an inflammatory potential (Murali et al 2015). This is a consequence of the fact that LPS can bind to all kinds of surfaces and thus represents a ubiquitous contaminant in all types of biomaterials (Gorbet and Sefton 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have been reported by other investigators [148][149] , and it has been repeatedly shown that surface chemistry plays an important role in cellular internalization.…”
Section: Tem Images (Figures 310a and 310b) Show The Presence Of Qds supporting
confidence: 91%
“…The results reported are inconsistent or unclear regarding whether PEGylation improves the uptake of intact nanoparticles across the epithelial tissues. For example, a study reported that 45 -70 nm polystyrene nanoparticles with PEGylated surfaces showed almost no uptake into microglial cells following 1 h incubation with neural cells whereas carboxylated surface functionalization showed significantly higher uptake into those cells 149 . This result is somewhat in agreement with the findings from presenty study using PEG-QDs administered intranasally in mice, which showed no accumulation in deeper nasal tissues compared to COOH-QDs.…”
Section: Uptakementioning
confidence: 99%